Persekitaran Ruang Rumah: Hubungannya dengan Salah Laku Remaja (Jurnal Pembangunan Sosial, 2013)
This study is an attempt to identify the relationship between housing space environment and adolescence misconduct, such as crime and aggression in a low cost housing area. The objective of the study is to identify the satisfaction towards physical and environment of low cost housing and its relationship with adolescence misconduct. A total of 333 sub-sample of parent’s and 333 sub-sample of adolescence had been randomly as study samples Result showed that there was no significant relationship between the physical and environment housing space with the adolescence misconduct (p>0.01). There was also no significant difference of the physical and environment housing space based on the parent’s ethnicity (p>0.01). Therefore, the physical and environment housing space had no significant impact on the adolescence misconduct.